Dengue: Status of current and under‐development vaccines - Redoni, M; Yacoub, S; Rivino, L; Giacobbe, DR; Luzzati, R; Di Bella, S (Wiley, 2020)
Dengue is an emerging mosquito‐borne viral infection with increasing reports of outbreaks. The clinical picture ranges from a benign febrile illness through to severe and potentially fatal manifestations. No specific anti‐viral treatment exists, and therapy only consists of supportive care. During the last three decades, several attempts to develop an effective vaccine have been made. The first dengue vaccine to obtain licensure was Dengvaxia, which was authorized in 2015 and is currently available in over 20 countries. Its use has been approved with strict limitations regarding age and serostatus of the recipients, highlighting the necessity for a more safe and efficacious vaccine. At present several vaccine, candidates are undergoing clinical and pre‐clinical trials. The most advanced candidates are TDV and TDV 003/005, two live‐attenuated vaccines, but another 15 vaccines are under development, introducing novel immunization strategies to the traditional dengue vaccine scenario. This work reviews the current research status on dengue vaccines.